2012
DOI: 10.1111/j.1439-0396.2012.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study at two different altitudes with two dietary nutrition levels on rumen fermentation and energy metabolism in Chinese Holstein cows

Abstract: The object of this study was to investigate the effect of two altitudes (1600 vs. 3600 m) with two nutritional levels [5.88 MJ/kg dry matter (DM) vs. 7.56 MJ/kg DM] on apparent total tract digestibility, rumen fermentation, energy metabolism, milk yield and milk composition in Chinese Holstein cows. Sixteen Chinese Holstein cows in their third lactation with close body weights, days in milk and milk yield were randomly divided into four groups, of which two were directly transferred from Lanzhou (altitude of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(54 reference statements)
1
6
1
Order By: Relevance
“…For their interpretation it is important to keep in mind that the factor ‘pasture site’ inseparably included individual effects of forage quality, amount of forage biomass on offer, altitude, the progressing stage of lactation and interactions among these factors. Generally, MY is impaired with increasing altitude, as has been reported for instance by Qiao et al ( 2013 ) for Chinese Holstein cattle kept at 3,600 m a.s.l. as compared to 1600 m a.s.l.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…For their interpretation it is important to keep in mind that the factor ‘pasture site’ inseparably included individual effects of forage quality, amount of forage biomass on offer, altitude, the progressing stage of lactation and interactions among these factors. Generally, MY is impaired with increasing altitude, as has been reported for instance by Qiao et al ( 2013 ) for Chinese Holstein cattle kept at 3,600 m a.s.l. as compared to 1600 m a.s.l.…”
Section: Discussionsupporting
confidence: 53%
“…Grazing at both, the highest altitude Site 3 (4,500 m) and Site 5, obviously resulted in an energy deficiency in the hybrids as indicated by BW changes, the first likely because of hypoxia (Bianca 1976 ) and the last due to the low forage quality. The BW gain found on Site 4 compared to Site 3 might indicate that this altitude was more comfortable for the hybrids whereas their high altitude tolerance was surpassed at 4,500 m. Fully adapted animals staying most of the time at very high altitude such as the yaks in the present study do not show such BW losses (Bartl et al 2009 ; Qiao et al 2013 ).…”
Section: Discussionmentioning
confidence: 47%
“…To our knowledge, this is the first measure of milk quality in a HA-adapted population of a small species. Milk quality also does not appear to change with adaptation to HA in larger mammals as there was no association between milk energy content and native elevation in humans, yaks or dairy cows (Bartl et al, 2009;Qiao et al, 2013;Barsila et al, 2014;Quinn et al, 2016). We also found that during a single nursing bout early in lactation (P8), litters gained between 0.20 and 0.31 g h −1 regardless of altitude ancestry.…”
Section: Altitude Ancestry Alters Maternal Carementioning
confidence: 62%
“…LA-native wild house mice (Mus musculus) raised for 10 generations in the cold (3°C) produce high fat content milk, which improves offspring growth and body composition (Barnett and Dickson, 1984). It is possible that small HA mammals also increase the fat content of their milk, although this has not been seen in the few large HA mammals studied to date (humans, yaks and dairy cows: Barsila et al, 2014;Bartl et al, 2009;Qiao et al, 2013;Quinn et al, 2016). Therefore, the mechanism by which HA mothers produce enough milk to provision their offspring is unclear.…”
Section: Maternal Care From Birth To Weaningmentioning
confidence: 99%